Polarized X-ray scattering measures molecular orientation in polymer-grafted nanoparticles - Subhrangsu Mukherjee (Nature Portfolio, 2021)
The orientation of polymer chains in the corona of polymer-grafted nanoparticles has never been measured. Here, the authors use polarized resonant soft X-ray scattering to measure local chain orientation in polystyrene grafted gold nanoparticles and quantify the thickness of the anisotropic region of the corona as well as the extent of chain orientation within it.